A Study of Culture-Specific Items (CSIs) and Translation Strategies in The Blind Earthworm in the Labyrinth - Prompan, Jantra (Rajapark Journal, 2024)
This research aims to investigate culture-specific items (CSIs) within the novel The Blind Earthworm in the Labyrinth and to analyze the translation strategies implemented by the translator when dealing with these culturally specific items. Employing a qualitative methodology, this study primarily emphasizes content analysis. The texts under study are the 2015 South East Asian Writers (“S.E.A. Write”) Award-winning Thai novel, The Blind Earthworm in the Labyrinth by Veeraporn Nitiprapha, alongside its English translation by Kong Rithdee in 2018. The research framework draws upon Nida’s (1964) cultural categories and Newmark’s (1988) translation strategies, providing a theoretical lens to examine the translator’s approaches to managing the non-equivalence between English and Thai. Findings revealed that the highest frequency among culture-specific items is attributed to material culture, followed by ecological, social, linguistic, and religious cultures, respectively. Among the 18 identified translation strategies, the most frequently employed was a literal translation, followed by couplets, transference, functional equivalent, cultural equivalent, compensation, paraphrase, reduction, shifts or transpositions, recognized translation, through-translation, descriptive equivalent, modulation, componential analysis, and a more specific word. Notably, synonyms, translation labels, and less expressive words were the least utilized. The findings suggest that these diverse strategies effectively address cultural disparities between Thai and English, providing valuable insights for Thai translators and Thai teachers in the field of translation. Recommendations for further research are also provided.